Determinants of healthcare seeking and out-of-pocket expenditures in a “free” healthcare system: evidence from rural Malawi - Nakovics, Meike Irene; Brenner, Stephan; Kalmus, Olivier; De Allegri, Manuela (Health economics review, 2020)
Monitoring financial protection is a key component in achieving Universal Health Coverage, even for health systems that grant their citizens access to care free-of-charge. Our study investigated out-of-pocket expenditure (OOPE) on curative healthcare services and their determinants in rural Malawi, a country that has consistently aimed at providing free healthcare services.
Gesehen am 30.07.2020
Keywords: Aufsatz in Zeitschrift